Penilaian Perilaku Budaya Keselamatan Dan Kesehatan Pekerja Menggunakan Model Antecedents Behavior Consequence (ABC) Pada Pekerja Produksi Hose Divisi Mandrel - Noviany, Irmadewi; Suryadi, Akmal (Ekonomis: Journal of Economics and Business, 2026)
The goal of occupational safety is to protect employees and others from potentially hazardous situations involving machinery, equipment, materials, and energy. Workplace accidents can be reduced and prevented by improving safe behavior using a behavioral approach. The ABC model stands for Antecedents-Behavior-Consequences. The validity test results table shows that 8 variables—safe behavior, PPE availability, knowledge, OHS communication media, coworkers, rewards, punishments, and physical injuries—are considered valid. This study found that 80 percent of occupational safety and health culture values are reflected in safe behavior, and 20 percent are reflected in unsafe behavior. Unsafe behaviors committed by mandrel workers, such as not wearing gloves during the striping process or not wearing a helmet while working, are violations of these values. Changes in critical behavior among workers in the Mandrel Division are due to consequences that can increase or decrease the emergence of critical behavior. One such consequence is the provision of awards or incentives to employees or teams that demonstrate high compliance with OHS practices.